The Book “Al-Iqleed” of Tadj Ad-Deen Al-Jendy - Ш.Т., Керім; А.Р., Альмухaметов (Journal of Oriental Studies, 2019)
The article studies about Tadj ad-deen Ahmad ibn Mahmoud ibn Omar al-Jendy’s works who was born in a medieval town Jent (died in 700/1301, currently, the Kyzylorda region, Kazakhstan). He is the famous linguist, the author of significant works on Arabic grammar. The article analyzes the character, substance, and the value of his famous book “Al-Iqleed” (Key). Al-Iqeed is the comment on the book “Mufassal” by Abu al-Kasym Mahmoud ibn Omar of az-Zamakhshari, which is considered as a classic work on Arabic grammar. In al-Iqleed are given important and reasonable comments on Az-Zamakhshary’s book. Moreover, Quranic texts and texts of Hadiths, proverbs and sayings, aphorisms and also works of poetry according to grammar rules are provided as examples. The grammatical analysis that Al-Jendy uses in his research is not repeated in any other remained comments made on this book by different authors. The author concentrated his attention on examining of ambiguously resolved issues in Arabic grammar, trying to find the most exact interpretation and the hidden sense in word meaning. Key words: Arabic grammar, linguist, Qur’an, word, explanation, rule, school of Basra and Kufa, imam, Islam.